Herrschaft und Repräsentation in der Habsburgermonarchie (1700-1740) Die kaiserliche Familie, die habsburgischen Länder und das Reich - Sommer-Mathis, Andrea 1956-; Weigl, Andreas 1961-; Forgó, András 1977-; Lörnitzo, Anna; Backerra, Charlotte 1983-; Lipp, Danièle; Garms-Cornides, Elisabeth 1944-; Göse, Frank 1957-; Polleroß, Friedrich 1958-; Hertel, Sandra 1984-; Kalmár, János 1952-; Auer, Leopold 1944-; et al. (bibliothek altes Reich, 2020)
Charles VI (1685-1740) was the first Habsburg ruler since Charles V with a personal claim to the Spanish crown, Austrian sovereignty, and Holy Roman emperorship. This volume examines various facets of his governance and representation, including the fiscal administration of the lands, communication between the imperial residential city and local and regional political actors, and the medial communication of power